Asymptotics of Type I Hermite–Padé Polynomials for Semiclassical Functions - Martínez-Finkelshtein, Andrei; Rakhmanov, Evguenii A.; Suetin, Sergey P. (Modern Trends in Constructive Function Theory, 2016)
Type I Hermite–Padé polynomials for a set of functions We discuss in more detail the case when From methodological considerations and in order to make the situation clearer, we start our exposition with the better known case of Padé approximants (when